Method for preparing polyglycolide under catalysis of metal-based ionic liquid

By using metal-based ionic liquid catalysts to promote the ring-opening polymerization of glycolide, the problems of toxicity and complex preparation of tin-based catalysts have been solved, and efficient, low-residue polyethylene glycolide preparation has been achieved, which is suitable for medical sutures and food packaging.

CN121086205APending Publication Date: 2025-12-09ZHENGZHOU ZHONGKE EMERGING IND TECH RES INST +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511351168.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-22
Publication Date
2025-12-09

AI Technical Summary

Technical Problem

In existing polyglycolic acid (PEG) preparation processes, the toxicity of tin-based catalysts poses a biosafety risk, and the preparation processes of existing low-toxicity or non-toxic catalysts are complex and difficult to meet the needs of medical sutures and food packaging.

Method used

Using metal-based ionic liquids as catalysts, the ring-opening polymerization of glycolide is catalyzed in a homogeneous manner. The hydrogen bonds and ionic microenvironment in the ionic liquid promote the reaction, reduce metal residue, and improve catalytic efficiency.

Benefits of technology

This method achieves highly efficient catalytic ring-opening polymerization of glycolide, reduces metal residue, improves the biosafety of polyethylene glycolide, and simplifies the catalyst preparation process, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and provides a method for preparing polyglycolide through catalysis of metal-based ionic liquid. The method comprises the following steps: mixing a metal-based ionic liquid solution and an initiator solution in a nitrogen atmosphere, and removing a solvent to obtain a mixed solution; adding glycolide into the mixed solution to obtain a homogeneous-phase mixed solution; and carrying out ring-opening polymerization reaction on the homogeneous-phase mixed solution. The adopted metal-based ionic liquid catalyst belongs to homogeneous catalysis in the ring-opening polymerization reaction of the glycolide, on one hand, the contact area between metal active sites and the glycolide can be increased, the ring-opening polymerization activity can be improved, on the other hand, hydrogen bonds or an ionic microenvironment in the ionic liquid can promote ring opening of the glycolide, and therefore the dosage of the catalyst is reduced, and the cost is reduced. Meanwhile, metal residues in the polyglycolide are reduced, and the biological safety of the polyglycolide is improved; the metal-based ionic liquid catalyst is simple in preparation process, easy for industrial production and high in catalytic efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, and in particular to a method for preparing polyglycolic acid by metal-based ionic liquid catalysis. Background Technology

[0002] Poly(lactic-coated lactide) is a widely used, fully biodegradable material. Currently, the main preparation process for polyethylene glycol (PEG) is the ring-opening polymerization method, which uses high-purity PEG (≥99.5%) as raw material and, under the action of an initiator and catalyst, produces PEG through a ring-opening polymerization reaction. Tin-based catalysts, such as stannous octoate or stannous chloride, are commonly used in the industrial production of PEG via ring-opening polymerization. However, the toxicity of metallic tin poses a threat to the biosafety of PEG products. Therefore, current research focuses primarily on the development of low-toxicity or non-toxic catalysts to reduce the toxicity of PEG products, enabling their use in medical sutures, food packaging, and agriculture.

[0003] Patent CN119320488A reports a method for preparing polyacetal alcohol (i.e., polyglycolic acid) using green and friendly zinc amino acid as a polymerization catalyst. This catalyst not only has good biocompatibility but also high nucleation efficiency, which can improve the molecular weight and purity of polyglycolic acid, making it show great application potential in high-end medical fields. Patents CN119119400A, CN118085255A, and CN118085254A disclose methods for preparing polyglycolic acid by catalyzing the ring-opening polymerization of glycolide using polymerizable Schiff base metals, six-center Schiff base metals, and eight-center Schiff base metals, respectively. The multinuclear synergistic effect within the Schiff base catalyst molecule effectively improves the ring-opening polymerization rate of glycolide, and the yield of polyglycolic acid can reach 96.4%–97.2%. However, the preparation method of Schiff base catalysts is extremely complex, which greatly limits its industrial application. Patent CN120005160A discloses an organic-base / thiourea binary catalytic system for the synthesis of polyglycolic acid (PEG). The abundant intramolecular hydrogen bonds in this catalyst increase catalytic activity, improve monomer conversion, and reduce side reactions. Furthermore, it leaves no metal residue, which is beneficial for the production of medical-grade PEG. However, the organic-base / thiourea binary catalyst also suffers from a complex preparation process. Moreover, the PEG obtained from this catalyst system has a molecular weight of only 26100 Da, which cannot meet the strength requirements for medical surgical sutures or tissue scaffolds.

[0004] In summary, the development of green and safe catalysts with high catalytic activity and simple preparation processes remains crucial in the synthesis of polyethylene glycol (PEG). Ionic liquids, a novel type of catalyst composed of cations and anions with a designable structure, possess excellent fluidity, high thermal stability, and tunable active sites. Hydrogen bonds and the ionic microenvironment within ionic liquids can promote substrate activation, improving conversion and product selectivity. Therefore, introducing metal active sites into ionic liquids to obtain metal-based ionic liquids holds promise for promoting the ring-opening of PEG, enhancing its ring-opening polymerization activity, while simultaneously reducing metal residue and improving biosafety. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing polyglycolic acid by metal-based ionic liquid catalysis, addressing the shortcomings of existing technologies.

[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution:

[0007] This invention provides a method for preparing polyglycolic acid (PEG) using a metal-based ionic liquid catalyst, comprising the following steps:

[0008] 1) Under a nitrogen atmosphere, the metal-based ionic liquid solution and the initiator solution are mixed, and the solvent is removed to obtain a mixture;

[0009] 2) Add glycolide to the mixture to obtain a homogeneous mixture;

[0010] 3) The homogeneous mixture undergoes ring-opening polymerization to obtain polyglycolic acid.

[0011] Preferably, the initiator in the initiator solution in step 1) is dodecyl alcohol or butanediol, and the solvent in the initiator solution includes one or more of toluene, dichloromethane and acetone;

[0012] The concentration of the initiator solution is 1–10 g / L.

[0013] Preferably, the concentration of the metal-based ionic liquid in the metal-based ionic liquid solution in step 1) is 0.5–2 g / L, and the solvent in the metal-based ionic liquid solution includes one or more of acetonitrile, dichloromethane, and acetone.

[0014] Preferably, the metal-based ionic liquid is prepared by a complexation reaction between an ionic liquid and a metal halide.

[0015] Preferably, the ionic liquid is an imidazole type ionic liquid;

[0016] The metal halide comprises one or more of stannous chloride, aluminum chloride, zinc chloride, stannous bromide, aluminum bromide, and zinc bromide.

[0017] Preferably, the molar ratio of the ionic liquid to the metal halide is 1:0.5 to 3;

[0018] The complexation reaction is carried out at a temperature of 120–180°C for a duration of 12–36 hours. Preferably, the complexation reaction is performed with stirring at a speed of 50–200 rpm.

[0019] Preferably, the mass ratio of glycolide to initiator is 5:0.001 to 0.02, and the mass ratio of glycolide to metal-based ionic liquid is 5:0.000125 to 0.0025.

[0020] Preferably, the ring-opening polymerization reaction is carried out at a temperature of 170–200°C and for a duration of 0.5–10 h.

[0021] The beneficial effects of this invention are:

[0022] 1) The metal-based ionic liquid catalyst used in this invention is a homogeneous catalyst in the ring-opening polymerization of glycolide. On the one hand, it can increase the contact area between the metal active sites and glycolide, thereby improving the ring-opening polymerization activity. On the other hand, the hydrogen bonds or ionic microenvironment in the ionic liquid can also promote the ring-opening of glycolide, thereby reducing the amount of catalyst required and reducing the metal residue in polyethylene glycolide, thus improving the biosafety of polyethylene glycolide. The metal-based ionic liquid catalyst has a simple preparation process, is easy to industrialize, and has high catalytic efficiency.

[0023] 2) This invention uses glycolide as raw material and metal-based ionic liquid as catalyst. Under the action of an initiator, the mixture is first melt-mixed and then ring-opened polymerized, which solves the problems of low catalytic efficiency and high metal residue in the prior art. Detailed Implementation

[0024] This invention provides a method for preparing polyglycolic acid (PEG) using a metal-based ionic liquid catalyst, comprising the following steps:

[0025] 1) Under a nitrogen atmosphere, the metal-based ionic liquid solution and the initiator solution are mixed, and the solvent is removed to obtain a mixture;

[0026] 2) Add glycolide to the mixture to obtain a homogeneous mixture;

[0027] 3) The homogeneous mixture undergoes ring-opening polymerization to obtain polyglycolic acid.

[0028] In this invention, the initiator in the initiator solution in step 1) is preferably dodecyl alcohol or butanediol, and the solvent in the initiator solution preferably includes one or more of toluene, dichloromethane and acetone;

[0029] The concentration of the initiator solution is preferably 1-10 g / L, more preferably 2-8 g / L, and even more preferably 4-6 g / L.

[0030] In this invention, the concentration of the metal-based ionic liquid in the metal-based ionic liquid solution in step 1) is preferably 0.5-2 g / L, more preferably 0.8-1.5 g / L, and even more preferably 1-1.2 g / L; the solvent in the metal-based ionic liquid solution preferably includes one or more of acetonitrile, dichloromethane, and acetone.

[0031] In this invention, the metal-based ionic liquid is preferably prepared by a complexation reaction between an ionic liquid and a metal halide.

[0032] In this invention, the ionic liquid is preferably an imidazole-type ionic liquid;

[0033] The metal halide preferably includes one or more of stannous chloride, aluminum chloride, zinc chloride, stannous bromide, aluminum bromide, and zinc bromide.

[0034] In this invention, the imidazole-type ionic liquid preferably comprises 1-alkyl-3-methylimidazolium chloride and / or 1-alkyl-3-methylimidazolium bromide;

[0035] The alkyl group is preferably a straight-chain alkyl group, and the number of carbon atoms in the straight-chain alkyl group is preferably 1 to 16, more preferably 2 to 12, and even more preferably 4 to 8.

[0036] In this invention, the molar ratio of the ionic liquid to the metal halide is preferably 1:0.5 to 3, more preferably 1:1 to 2.5, and even more preferably 1:1.5 to 2;

[0037] The temperature of the complexation reaction is preferably 120–180°C, more preferably 130–170°C, and even more preferably 140–160°C; the time of the complexation reaction is preferably 12–36 h, more preferably 18–30 h, and even more preferably 24 h.

[0038] In this invention, stirring is preferably performed during the complexation reaction, and the stirring speed is preferably 50-200 rpm, more preferably 100-150 rpm, and even more preferably 150 rpm.

[0039] In this invention, the metal-based ionic liquid preferably comprises one or more of the following: 1-ethyl-3-methylimidazolium-stannous chloride, 1-butyl-3-methylimidazolium-stannous chloride, 1-octyl-3-methylimidazolium-stannous chloride, 1-dodecyl-3-methylimidazolium-stannous chloride, 1-hexadecyl-3-methylimidazolium-stannous chloride, 1-butyl-3-methylimidazolium-zinc chloride, 1-butyl-3-methylimidazolium-aluminum chloride, 1-butyl-3-methylimidazolium-stannous bromide, 1-butyl-3-methylimidazolium-zinc bromide, and 1-butyl-3-methylimidazolium-aluminum bromide.

[0040] In this invention, the temperature for removing the solvent in step 1) is preferably 50-80°C, more preferably 60-70°C; the vacuum degree for removing the solvent is preferably 10-30 mbar, more preferably 20 mbar; and the time for removing the solvent is preferably 20-40 min, more preferably 30 min.

[0041] In this invention, the mass ratio of glycolide to initiator is preferably 5:0.001-0.02, more preferably 5:0.004-0.016, and even more preferably 5:0.008-0.012; the mass ratio of glycolide to metal-based ionic liquid is preferably 5:0.000125-0.0025, more preferably 5:0.0002-0.00125, and even more preferably 5:0.00025-0.0005.

[0042] In this invention, after the glycolide in step 2) is added to the mixture, it is preferable to heat and stir to melt the glycolide, thereby obtaining a homogeneous mixture;

[0043] The temperature is preferably raised to 80-120°C, more preferably to 90-110°C, and even more preferably to 100°C; the stirring speed is preferably 50-200 rpm, more preferably 100-150 rpm, and even more preferably 150 rpm; the stirring time is preferably 0.1-2 h, more preferably 0.5-1.5 h, and even more preferably 1 h.

[0044] In this invention, the temperature of the ring-opening polymerization reaction is preferably 170-200°C, more preferably 180-190°C; the time of the ring-opening polymerization reaction is preferably 0.5-10 h, more preferably 1-5 h, and even more preferably 2-4 h.

[0045] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0046] Example 1

[0047] The metal-based ionic liquid is 1-ethyl-3-methylimidazolium-stannous chloride. The preparation method is as follows: 1-ethyl-3-methylimidazolium chloride and stannous chloride in a molar ratio of 1:2 are complexed at 160°C and 150 rpm for 12 h to obtain 1-ethyl-3-methylimidazolium-stannous chloride.

[0048] Under nitrogen purging, 2 mL of a 4 g / L toluene solution of dodecanol and 250 μL of a 1 g / L acetonitrile solution of a metal-based ionic liquid were added to a 100 mL reaction flask with a side-tube glass gate. The mixture was heated to 60 °C in an oil bath and the solvent was removed at 20 mbar for 30 min to obtain a mixture. After cooling to room temperature, 5 g of glycolide was added to the reaction flask under nitrogen purging, and nitrogen purging was continued for 5 min to remove air from the flask before sealing. The reaction flask was placed in a 100 °C oil bath and stirred at 100 rpm for 0.5 h to completely melt the glycolide, resulting in a homogeneous mixture. The reaction flask was heated to 180 °C and subjected to ring-opening polymerization for 1 h to obtain polyglycolic acid (PEG). The weight-average molecular weight of PEG was determined by gel permeation chromatography, and the metal residue in PEG was determined by inductively coupled plasma atomic emission spectrometry (ICP-AES).

[0049] The polyglycolic acid obtained in this example is pale yellow, weighs 4.76 g, has a yield of 95.2%, a weight-average molecular weight of 105368 Da, and a tin content of 15.7 ppm.

[0050] Example 2

[0051] The metal-based ionic liquid in Example 1 was replaced with 1-butyl-3-methylimidazolium-stannous chloride, and everything else remained the same as in Example 1. The preparation method of 1-butyl-3-methylimidazolium-stannous chloride was as follows: 1-butyl-3-methylimidazolium chloride and stannous chloride in a molar ratio of 1:2 were complexed at 160°C and 150 rpm for 24 h to obtain 1-butyl-3-methylimidazolium-stannous chloride.

[0052] The polyglycolic acid obtained in this example is pale yellow, weighs 4.80 g, has a yield of 96.0%, a weight-average molecular weight of 115103 Da, and a tin content of 14.6 ppm.

[0053] Example 3

[0054] The metal-based ionic liquid in Example 1 was replaced with 1-octyl-3-methylimidazolium-stannous chloride, and everything else remained the same as in Example 1. The preparation method of 1-octyl-3-methylimidazolium-stannous chloride was as follows: 1-octyl-3-methylimidazolium chloride and stannous chloride in a molar ratio of 1:2 were complexed at 180°C and 150 rpm for 36 h to obtain 1-octyl-3-methylimidazolium-stannous chloride.

[0055] The polyglycolic acid obtained in this example is pale yellow, weighs 4.75 g, has a yield of 95%, a weight-average molecular weight of 101476 Da, and a tin content of 13.6 ppm.

[0056] Example 4

[0057] The metal-based ionic liquid in Example 1 was replaced with 1-dodecyl-3-methylimidazolium-stannous chloride, and everything else remained the same as in Example 1. The preparation method of 1-dodecyl-3-methylimidazolium-stannous chloride was as follows: 1-dodecyl-3-methylimidazolium chloride and stannous chloride in a molar ratio of 1:2 were complexed at 160°C and 150 rpm for 36 h to obtain 1-dodecyl-3-methylimidazolium-stannous chloride.

[0058] The polyglycolic acid obtained in this example is pale yellow, weighs 4.78 g, has a yield of 95.6%, a weight-average molecular weight of 100429 Da, and a tin content of 11.5 ppm.

[0059] Example 5

[0060] The metal-based ionic liquid in Example 1 was replaced with 1-hexadecyl-3-methylimidazolium-stannous chloride, and everything else remained the same as in Example 1. The preparation method of 1-hexadecyl-3-methylimidazolium-stannous chloride was as follows: 1-hexadecyl-3-methylimidazolium chloride and stannous chloride in a molar ratio of 1:2 were complexed at 160°C and 150 rpm for 36 h to obtain 1-hexadecyl-3-methylimidazolium-stannous chloride.

[0061] The polyglycolic acid obtained in this example is pale yellow, weighs 4.77 g, has a yield of 95.4%, a weight-average molecular weight of 102865 Da, and a tin content of 10.2 ppm.

[0062] Example 6

[0063] The metal-based ionic liquid is 1-butyl-3-methylimidazolium chloride salt. The preparation method is as follows: 1-butyl-3-methylimidazolium chloride salt and zinc chloride in a molar ratio of 1:2 are complexed at 120℃ and 100 rpm for 12 h to obtain 1-butyl-3-methylimidazolium chloride salt.

[0064] Under nitrogen purging, 2 mL of a toluene solution of dodecanol (8 g / L) and 1.25 mL of an acetonitrile solution of a metal-based ionic liquid (1 g / L) were added to a 100 mL reaction flask with a side-tube glass gate. The mixture was heated to 60 °C in an oil bath and the solvent was removed at 20 mbar for 30 min to obtain a mixture. After cooling to room temperature, 5 g of glycolide was added to the reaction flask under nitrogen purging, and nitrogen purging was continued for 5 min to remove air from the flask before sealing. The reaction flask was placed in a 110 °C oil bath and stirred at 100 rpm for 1 h to completely melt the glycolide, obtaining a homogeneous mixture. The reaction flask was heated to 190 °C and a ring-opening polymerization reaction was carried out at 190 °C for 4 h to obtain polyglycolic acid (PEG). The weight-average molecular weight of PEG was determined by gel permeation chromatography, and the metal residue in PEG was determined by inductively coupled plasma atomic emission spectrometry (ICP-AES).

[0065] The polyglycolic acid obtained in this example is pale yellow, weighs 4.77 g, has a yield of 95.4%, a weight-average molecular weight of 84450 Da, and a zinc content of 71.2 ppm.

[0066] Example 7

[0067] The metal-based ionic liquid is 1-butyl-3-methylimidazolium-aluminum chloride salt. The preparation method is as follows: 1-butyl-3-methylimidazolium chloride and aluminum chloride in a molar ratio of 1:2 are complexed at 140℃ and 200 rpm for 24 h to obtain 1-butyl-3-methylimidazolium-aluminum chloride salt.

[0068] Under nitrogen purging, 2 mL of a 5 g / L toluene solution of dodecanol and 1.25 mL of a 2 g / L acetonitrile solution of a metal-based ionic liquid were added to a 100 mL reaction flask with a side-tube glass gate. The mixture was heated to 60 °C in an oil bath and the solvent was removed at 20 mbar for 30 min to obtain a mixture. After cooling to room temperature, 5 g of glycolide was added to the reaction flask under nitrogen purging, and nitrogen purging was continued for 5 min to remove air from the flask before sealing. The reaction flask was placed in a 110 °C oil bath and stirred at 100 rpm for 2 h to completely melt the glycolide, resulting in a homogeneous mixture. The reaction flask was heated to 200 °C and subjected to a ring-opening polymerization reaction at 200 °C for 5 h to obtain polyglycolic acid (PEG). The weight-average molecular weight of PEG was determined by gel permeation chromatography, and the metal residue in PEG was determined by inductively coupled plasma atomic emission spectrometry (ICP-AES).

[0069] The polyglycolic acid obtained in this example is brown, weighs 4.80 g, has a yield of 96.0%, a weight-average molecular weight of 51862 Da, and an aluminum content of 58.7 ppm.

[0070] Example 8

[0071] The ring-opening polymerization temperature in Example 2 was modified to 200℃, and everything else remained the same as in Example 2.

[0072] The polyglycolic acid obtained in this example is yellow, weighs 4.88 g, has a yield of 97.6%, a weight-average molecular weight of 125869 Da, and a tin content of 13.7 ppm.

[0073] Example 9

[0074] The ring-opening polymerization temperature in Example 2 was modified to 170°C, and everything else remained the same as in Example 2.

[0075] The polyglycolic acid obtained in this example is pale yellow, weighs 4.76 g, has a yield of 95.2%, a weight-average molecular weight of 101648 Da, and a tin content of 15.3 ppm.

[0076] Example 10

[0077] The molar ratio of 1-butyl-3-methylimidazolium chloride and stannous chloride in the metal-based ionic liquid of Example 2 was changed to 1:1.5, and the rest was the same as in Example 2.

[0078] The polyglycolic acid obtained in this example is yellow, weighs 4.81 g, has a yield of 96.2%, a weight-average molecular weight of 98652 Da, and a tin content of 12.6 ppm.

[0079] Example 11

[0080] The molar ratio of 1-butyl-3-methylimidazolium chloride and stannous chloride in the metal-based ionic liquid of Example 2 was changed to 1:3, and the rest was the same as in Example 2.

[0081] The polyglycolic acid obtained in this example is yellow, weighs 4.78 g, has a yield of 95.6%, a weight-average molecular weight of 95615 Da, and a tin content of 17.9 ppm.

[0082] Example 12

[0083] The ring-opening polymerization time in Example 2 was modified to 10 hours, while the rest remained the same as in Example 2.

[0084] The polyglycolic acid obtained in this example is yellow, weighs 4.86 g, has a yield of 97.2%, a weight-average molecular weight of 116523 Da, and a tin content of 15.1 ppm.

[0085] Comparative Example 1

[0086] The metal-based ionic liquid in Example 2 was replaced with stannous chloride, and everything else was the same as in Example 2.

[0087] The polyglycolic acid obtained in this comparative example was pale yellow, with a mass of 4.79 g, a yield of 95.8%, a weight-average molecular weight of 105944 Da, and a tin content of 30.5 ppm.

[0088] Comparative Example 2

[0089] The metal-based ionic liquid in Example 6 was replaced with zinc chloride, and everything else was the same as in Example 6.

[0090] The polyglycolic acid obtained in this comparative example was pale yellow, with a mass of 4.75 g, a yield of 95.0%, a weight-average molecular weight of 79563 Da, and a zinc content of 126.3 ppm.

[0091] Comparative Example 3

[0092] The metal-based ionic liquid in Example 7 was replaced with aluminum chloride, and everything else was the same as in Example 7.

[0093] The polyglycolic acid obtained in this comparative example was brown, with a mass of 4.82 g, a yield of 96.4%, a weight-average molecular weight of 49584 Da, and an aluminum content of 105.8 ppm.

[0094] Comparative Example 4

[0095] The metal-based ionic liquid in Example 2 was replaced with 1-butyl-3-methylimidazolium chloride, and the rest was the same as in Example 2.

[0096] The polyglycolic acid obtained in this comparative example was brown, with a mass of 4.74 g, a yield of 94.8%, and a weight-average molecular weight of 28514 Da.

[0097] Analysis of Examples 1-5 and Comparative Example 1 shows that, compared with the traditional stannous chloride catalyst, Examples 1-5, using tin-based ionic liquids as catalysts, can obtain polyethylene glycol with a weight-average molecular weight of 100,000-120,000 under the same catalyst dosage. While meeting the molecular weight requirements of surgical sutures in the medical field, it can significantly reduce the tin content in polyethylene glycol, down to 10.2 ppm, achieving the preparation of polyethylene glycol with low tin residue. Examples 8-12, using tin-based ionic liquids as catalysts, changed the reaction conditions based on Example 2. Although the weight-average molecular weight of the obtained polyethylene glycol decreased slightly, it still maintained low tin residue. Examples 6 and 7, using zinc-based and aluminum-based ionic liquids as catalysts respectively, showed a significant reduction in metal residue in the obtained polyethylene glycol compared with Comparative Examples 2 and 3. Examples 1-12, using metal-based ionic liquids as catalysts, showed a significant increase in the weight-average molecular weight of the obtained polyethylene glycol compared with the polyethylene glycol product of Comparative Example 4 using ionic liquids as catalysts.

[0098] As can be seen from the above embodiments, the present invention provides a method for preparing polyglycolic acid by metal-based ionic liquid catalysis. The method uses metal-based ionic liquid as a catalyst to homogeneously catalyze the ring-opening polymerization reaction of glycolide, thereby improving catalytic efficiency, reducing catalyst dosage, reducing metal residue in glycolide, and improving the biosafety of glycolide.

[0099] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing polyglycolic acid using a metal-based ionic liquid catalyst, characterized in that, It includes the following steps: 1) Under a nitrogen atmosphere, the metal-based ionic liquid solution and the initiator solution are mixed, and the solvent is removed to obtain a mixture; 2) Add glycolide to the mixture to obtain a homogeneous mixture; 3) The homogeneous mixture undergoes ring-opening polymerization to obtain polyglycolic acid.

2. The method according to claim 1, characterized in that, Step 1) The initiator in the initiator solution is dodecyl alcohol or butanediol, and the solvent in the initiator solution includes one or more of toluene, dichloromethane and acetone; The concentration of the initiator solution is 1–10 g / L.

3. The method according to claim 1 or 2, characterized in that, In step 1), the concentration of the metal-based ionic liquid in the solution is 0.5–2 g / L, and the solvent in the solution includes one or more of acetonitrile, dichloromethane, and acetone.

4. The method according to claim 3, characterized in that, The metal-based ionic liquid is prepared by a complexation reaction between an ionic liquid and a metal halide.

5. The method according to claim 4, characterized in that, The ionic liquid is an imidazole type ionic liquid; The metal halide comprises one or more of stannous chloride, aluminum chloride, zinc chloride, stannous bromide, aluminum bromide, and zinc bromide.

6. The method according to claim 4 or 5, characterized in that, The molar ratio of the ionic liquid to the metal halide is 1:0.5 to 3; The complexation reaction is carried out at a temperature of 120–180°C for a duration of 12–36 h.

7. The method according to claim 6, characterized in that, The complexation reaction is carried out by stirring at a speed of 50 to 200 rpm.

8. The method according to claim 7, characterized in that, The mass ratio of glycolide to initiator is 5:0.001 to 0.02, and the mass ratio of glycolide to metal-based ionic liquid is 5:0.000125 to 0.0025.

9. The method according to claim 7 or 8, characterized in that, The ring-opening polymerization reaction is carried out at a temperature of 170–200°C for 0.5–10 h.

Citation Information

Patent Citations

  • Eight-center Schiff base metal catalyst, preparation method thereof and preparation method of polyglycolic acid

    CN118085254A

  • Six-center Schiff base metal catalyst, preparation method thereof and preparation method of polyglycolic acid

    CN118085255A

  • Polymeric Schiff base metal compound as well as preparation method and application thereof

    CN119119400A

  • Polyglycolic acid and preparation method thereof

    CN119320488A

  • Binary catalytic system for polymerization reaction as well as preparation method and application of binary catalytic system

    CN120005160A